2013
DOI: 10.1080/08856257.2013.768453
|View full text |Cite
|
Sign up to set email alerts
|

Exploring opportunities available and perceived barriers to physical activity engagement in children and young people with Down syndrome

Abstract: Primary objective: The aim of this study was to explore physical activity amongst children and young people with Down syndrome. Method and procedures:The Youth Physical Activity Promotion Model (YPAP) (Welk 1999) was used to inform semi-structured interviews to explore physical activity of children and young people with Down syndrome.Participants were 3 males and 5 females, aged between 6 and 21 years (16.38 + 5.04 years (mean + SD)) who had been diagnosed with the condition Down syndrome. Dyadic interviews we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(108 citation statements)
references
References 20 publications
(31 reference statements)
13
44
0
Order By: Relevance
“…Recess provides a daily opportunity for discretionary PA in a safe, supervised environment. This is perhaps even more important for this population, where many barriers are perceived to exist to PA engagement outside the school environment (Downs et al, 2013;Downs et al, 2014). Participants within this study engaged in small group activities at generally low PA intensities.…”
Section: Implications For School Psychologistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recess provides a daily opportunity for discretionary PA in a safe, supervised environment. This is perhaps even more important for this population, where many barriers are perceived to exist to PA engagement outside the school environment (Downs et al, 2013;Downs et al, 2014). Participants within this study engaged in small group activities at generally low PA intensities.…”
Section: Implications For School Psychologistsmentioning
confidence: 99%
“…Recent, formative, qualitative studies have suggested that opportunities for children and young people with ID are limited outside the school setting in the UK (Downs, Boddy, Knowles, Fairclough, & Stratton, 2013;Downs et al, 2014), and that schools represent the most accessible opportunity for children and young people with ID to be physically active.…”
Section: Intellectual Disabilities and Recessmentioning
confidence: 99%
“…This result is consistent with previous research, which demonstrated how parents deliver emotional/motivational and economic support. These are necessary to face challenging tasks as well as the transportation and the costs of activities (Badia et al, 2011;Downs et al, 2013;Mahy et al, 2010;Shikako-Thomas, Shevell, & Schmitz, 2013). The costs of sports programs, the equipment, and the transportation are expensive and rely on family available economical resourcess (Cordes & Howard, 2005;Van Naarden Braun, Yeargin-Allsopp, & Lollar, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indirect influence is played by personal demographics, such as age, ethnicity, and socioeconomic status. Recently, an adapted model of the YPAP was developed by Downs, Boddy, Knowles, Fairclough, and Stratton (2013). It included enabling, predisposing, and reinforcing factors to PA for children with DS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation